Completeness of Facilities and Teacher Support for the Utilization of the Youth Counseling Information Center Program on Student’s Knowledge, Attitude, and Behavior at Bali Mandara Senior High School - Ketut Eka Larasati Wardana; Dyah Pradnyaparamita Duarsa; Ni Luh Putu Suariyani (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Adolescents are a group of people with a fairly high vulnerability to reproductive health problems in Indonesia. To reduce vulnerability to reproductive health problems, the Youth Counseling Information Center Program (PIK-R) program was introduced, one of which was at Bali Mandara senior high school, but its utilization was still low. The purpose of this study was to determine the relationship between completeness of facilities and teacher support on the knowledge, attitudes, and behavior of using youth counseling information center.Subjects and Method: The cross-sectional survey research was conducted on all students in Bali Mandara senior high school from October 2017 to March 2018. A total of 118 students were selected by total sampling. The dependent variables were knowledge, attitude, and behavior. The independent variables were youth counseling information center facilities and teacher support. Data were collected using a questionnaire and analyzed by a multiple logistic regression.Results: Factors related to student knowledge were completeness of facilities (aOR= 3.14; 95%CI= 1.25 to 7.85; p= 0.014) and teacher support (aOR= 3.22; 95% CI= 1.27 to 8.15; p= 0.013). Completeness of facilities (aOR= 9.26; 95% CI= 3.30 to 25.97; p= 0.001) and teacher support (aOR= 6.27; 95% CI= 2.23 to 17.59; p= 0.001) were associated with student attitude. While the factors related to the behavior of using youth counseling information center were the completeness of the facilities (aOR= 11.56; 95% CI= 3.96 to 33.70; p= 0.001) and teacher support (aOR= 4.59; 95% CI= 1.60 to 13.17; p= 0.005).Conclusion: The completeness of facilities and teacher support for the youth counseling information center program is related to the knowledge, attitudes, and behavior of using youth counseling information center.Keywords: youth counseling information center program, knowledge, attitude, behavior.Correspondence:Ketut Eka Larasati Wardana. Bali Mandara Senior High School. Jl. Raya Air Sanih, Kubutambahan, Kec. Kubutambahan, Kabupaten Buleleng, Bali 81172. Email: eka.larasati12@gmail.com.Journal of Health Promotion and Behavior (2022), 07(04): 356-362DOI: https://doi.org/10.26911/thejhpb.2022.07.04.08